A Sick Imagination: Pathologies and Errors in Judgment - Feloj, Serena (Con-Textos Kantianos. International Journal of Philosophy, 2022)
In this paper I will develop an investigation of mental illness in relation to errors of judgment. Even based on the rational/irrational opposition, during the 18th century reason is seen appropriating madness, and not only whenever it classifies mental illnesses and develops special scientific knowledge about them. More importantly, madness lurks in the very workings of modern reason. And of course, it sneaks into the error of judgment, making all border between the two very thin. A case can then be made for the complementarity between reason and madness. In this sense, madness finds a place in Kant’s project, from its very foundations. Recognizing the finiteness of the human intellect and stating accordingly the need for an exact survey of its limits means at the same time recognizing the possibility of error in judgment and the danger that knowledge may turn into madness. Provided one is to accept the methodological assumption that there is a continuity between the Transcendental Dialectic and the section of the Anthropology on judgment and mental illness, a constellation of essential Kantian notions comes to the fore as underpinning the overall transcendental project. A picture unfolds based on which error can affect, at the very least, perception, imagination and judgment. Errors of judgment, illusions, and madness are thus never far apart in Kant’s accounts on human faculties, their dialectical drifts, and the possibility of psychopathy.